Atrator no sentido pullback e trajetórias completas extremas para problemas governados pelo p-Laplaciano - Capelato, Erika (2011)
We study non-autonomous problems with the main part given by the p- Laplacian and establish existence results of pullback attractor, comparison of solutions and existence of a maximal and a minimal complete trajectories. In bounded smooth domains we assume rather general conditions on the perturbative operator and we admit the process associated with the problem being multivalued. We obtain analogous results for systems in Rn with further restrictions in perturbative terms in such way that we deal with a univocal process.